Entrepreneurial skills in Boyacá - Rodríguez Moreno, Diana Cristina; Gómez Murillo, Adriana Ximena (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper presents some reflections about entrepreneurial skills in the department of Boyacá, from the results obtained in 2013, during the development of the second regional entrepreneurship contest, whose process and results are also presented. For this work were selected some entrepreneur skills. Were applied tools using Likert scale for drawing up the skill level of entrepreneurs in Boyacá. The entrepreneurs have ability to achieve goals, low capacity for teamwork and weak leadership.